Anti-trafficking discourses, migration control and representations of trafficked women: The Portuguese case - Clemente, M. (Migration and education: To understand relations between migration and education: Challenges for research and practice, 2019)
Since the late 1990s, trafficking in human beings (THB) has received increasing international attention. The problem has attracted the attention of numerous States and non-governmental organizations, and has been considered as one of the priorities of the agenda of several international agencies.